Pendampingan Penasehan Hukum Terhadap Tersangka Dan Terdakwa Dalam Perkara Korupsi Di IKADIN Cirebon - Febia Putri Mulyana; Sugianto Sugianto; Saiful Ansori; Qisthi Fauziyyah Sugianto (Hukum, 2026)
Legal representation by advocates is essential to protecting the rights of corruption suspects and defendants and ensuring a fair criminal justice process. This study aims to analyze the legal assistance provided by members of the Cirebon branch of the Indonesian Advocates Association (IKADIN) to suspects and defendants in corruption cases and to assess its conformity with the principles of due process of law, the presumption of innocence, and Law Number 20 of 2025 concerning the Indonesian Criminal Procedure Code. This study employs an empirical legal method with a socio-legal approach and a qualitative case study design. Data were collected through semi-structured interviews with IKADIN Cirebon administrators and advocates, along with an examination of ethically accessible case documents, court decisions, and relevant legislation. The data were qualitatively analyzed through data condensation, data presentation, and conclusion drawing by examining the fulfillment of clients’ rights, advocates’ professional actions, organizational support, and obstacles to legal representation. The findings indicate that advocates’ assistance includes explaining clients’ rights, examining the legality of law enforcement measures, accompanying clients during questioning, analyzing indictments and evidence, preparing legal defenses, and advising clients on available legal remedies. Its implementation, however, continues to face challenges arising from the complexity of evidentiary issues in corruption cases, limited specialized competence, restricted access to clients and documents, uncertain financing, and public stigma. Strengthening legal representation requires professional service standards, training on the 2025 Criminal Procedure Code, team-based case management, pro bono services, ethical supervision, and interinstitutional coordination without compromising advocates’ independence.